Low Blue Dose Photodynamic Therapy with Porphyrin-Iron Oxide Nanoparticles Complexes: In Vitro Study on Human Melanoma Cells - Simona Nistorescu; Ana-Maria Udrea; Madalina Andreea Badea; Iulia Lungu; Mihai Boni; Tatiana Tozar; Florian Dumitrache; Valentin-Adrian Maraloiu; Roua Gabriela Popescu; Claudiu Fleaca; Ecaterina Andronescu; Anca Dinischiotu; et al. (MDPI AG, 2021)
The purpose of this study was to investigate the effectiveness in photodynamic therapy of iron oxide nanoparticles (γ-Fe2O3 NPs), synthesized by laser pyrolysis technique, functionalized with 5,10,15,20-(Tetra-4-sulfonatophenyl) porphyrin tetraammonium (TPPS) on human cutaneous melanoma cells, after only 1 min blue light exposure. The efficiency of porphyrin loading on the iron oxide nanocarriers was estimated by using absorption and FTIR spectroscopy. The singlet oxygen yield was determined via transient characteristics of singlet oxygen phosphorescence at 1270 nm both for porphyrin functionalized nanoparticles and rose bengal used as standard. The irradiation was performed with a LED (405 nm, 1 mW/cm2) for 1 min after melanoma cells were treated with TPPS functionalized iron oxide nanoparticles (γ-Fe2O3 NPs_TPPS) and incubated for 24 h. Biological tests revealed a high anticancer effect of γ-Fe2O3 NPs_TPPS complexes indi-cated by the inhibition of tumor cell proliferation, reduction of cell adhesion, and induction of cell death through ROS generated by TPPS under light exposure. The biological assays were combined with the pharmacokinetic prediction of the porphyrin.